Collaboration of Pentahelix in Community-Based Stunting Prevention Program in Tembelang District - Putri, Sephia Nurlista; Hardjati, Susi (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This article analyzes the policies implemented by the Tembelang Health Center to reduce stunting cases in Tembelang District, Jombang Regency. Through the analysis, it was found that the efforts implemented were by forming a Penta Helix collaboration involving five actors including academics, business, community, government, and media which were implemented in the